Perancangan User Experience e-Learning pada Website SMAN 13 Surabaya menggunakan Pendekatan Human Centered Design (HCD) - Dzakiyyah Salma Wachid; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
e-Learning is a tools for the learning process which is implemented without having to face to face directly between students and teachers. In e-learning usually contains information related to learning modules, school assignments, test score results and other announcements related to the learning process. E-Learning is usually one of the features on school websites. Based on the results of the author's interviews with several students and teachers, it is difficult to implemented the learning process with many kinds of platforms so they feel confused because the information is not well organized. So students and teachers need a platform that can help the learning process. With e-Learning, all information is clearly organized, so students and teachers can easily implemented the learning process without any reason to miss information. This study aims to design e-Learning on the website of SMAN 13 Surabaya, to meet user needs. In this study, the approach used is the Human Centered Design approach. Human Centered Design is an approach that uses human/ergonomic factors, knowledge and usability techniques. This approach is interactive and aims to develop systems in design that can increase the effectiveness and satisfaction of users. The resulting design is a desktop version of the prototype by testing using the User Experience Questionnaire (UEQ) to find out whether the user's needs have been resolved. The results of the test using the UEQ assessment, which have a positive category mean value with all UEQ scales being in the very good category except the Perspicuity scale being in the above average category and the Novelty scale being in the good category.